The Prevention of Peatland Fires in Indonesia: ‘Law in Action’ to Implement the ASEAN Haze Treaty - Myrna A Safitri (IKAT: The Indonesian Journal of Southeast Asian Studies, 2021)
Signed in 2002, the ASEAN Haze Treaty is expected to reduce transboundary haze pollution and improve regional environmental governance. Indonesia plays a vital role in the implementation of the Treaty's goals. It has the largest forest and peatland area in Southeast Asia. Yet, its repeated forest and land fires had often caused transboundary pollution. Since 2016 the Indonesian Government has improved its national laws and strengthened institutional aspects of peatland protection. The peatland ecosystem is essential because it is prone to burning. Unfortunately, few studies describe how these policy changes have impacted fire prevention in degraded peatland ecosystems. This article scrutinizes the political factors behind the legal and institutional changes in Indonesia's peatland governance during 2016-2020. The theory of legal culture becomes the primary reference in this regard. This article then identifies six predominant factors in peatland law improvement: strong leadership, improved coordination at the national and sub-national levels, making operational directives, establishing a specialized Government institution dealing with peatland restoration, law enforcement, and the strength of civil society in doing public oversight.